The Potential Protective Effect of Curcumin on Amyloid-β-42 Induced Cytotoxicity in HT-22 Cells. (15th January 2018) - Zhang, Lu; Fang, Yu; Cheng, Xuan; Lian, Yajun; Zeng, Zhaoshu; Wu, Chuanjie; Zhu, Hongcan; Xu, Hongliang
Abstract : Background . We aimed to investigate the effect and mechanism of curcumin (CUR) in Alzheimer's disease (AD). Methods . Mouse hippocampal neuronal cell line HT-22 was treated with A β 1–42 and/or CUR, and then cell viability was evaluated by cell counting kit 8, Beclin-l level was detected using western blotting, and the formation of autophagosomes was observed by transmission electron microscopy (TEM). Furthermore, transcriptome sequencing and analysis were performed in cells with A β 1–42 alone or A β 1–42 + CUR. Results . A β 1–42 treatment significantly inhibited cell viability compared with untreated cells( P < 0.01 ) . After treatment for 48 h, CUR remarkably promoted cell viability compared with cell treated with A β 1–42 alone( P < 0.01 ) . Compared with cells treated with A β 1–42 alone, the expression of Beclin-1 was slightly reduced in cells with combined treatment of A β 1–42 with CUR( P < 0.05 ) . Consistently, TEM results showed that CUR inhibited the formation of autophagosomes in cells treated with A β 1–42. Furthermore, the protein-protein interaction network showed five key genes, including MYC, Cdh1, Acaca, Egr1, and CCnd1, likely involved in CUR effects. Conclusions . CUR might have a potential neuroprotective effect by promoting cell viability in AD, which might be associated with cell autophagy. Furthermore, MYC, Cdh1, and Acaca might be involved in the progression of AD.